Manajemen Kurikulum dalam Meningkatkan Kesadaran Lingkungan Siswa Pada Pendidikan Menengah Islam - Hidayat, Randa Deski; Zebua, Ali Marzuki (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Schools as learning spaces and character builders have a crucial and strategic role in shaping student character, including instilling values of environmental awareness. This research aims to understand how curriculum management at MAN 1 Sungai Penuh can create students' environmental awareness through a qualitative case study approach. Data were obtained through interviews, observations, and documentation of the school and students. The results showed that planning involves Banglestari and PMR, organizing available resources such as cleaning tools in each class, implementation by emphasizing teachers to provide real examples, and evaluating the curriculum by providing environmentally oriented rewards and sanctions carried out at MAN 1 Sungai Penuh has integrated environmental values systematically. MAN 1 Sungai Penuh is able to send its students to be Green Generation representatives at the national level. However, challenges were also found such as the lack of sustainability of good facility management, especially since the covid-19 outbreak and support from the government and the internal motivation of some students. This research recommends strengthening collaboration, especially attention from related agencies and improving facilities as an effort to maintain the sustainability of environmental awareness that has been formed. It is equally important to create new innovations so that students are more interested in environmental health